2020
DOI: 10.3390/ijerph17062127
|View full text |Cite
|
Sign up to set email alerts
|

Global Research on Quality of Life of Patients with HIV/AIDS: Is It Socio-Culturally Addressed? (GAPRESEARCH)

Abstract: Quality of life (QOL) has been considered as an important outcome indicator in holistic care for HIV-infected people, especially as HIV/AIDS transforms from a fatal illness to a chronic condition. This study aimed to identify trends and emerging topics among research concerning the QOL of people living with HIV/AIDS (PLWHA). The analyzed data were English papers published from 1996 to 2017, searched and extracted from the Web of Science Core Collection. Collaborations between countries and the correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
(54 reference statements)
1
34
0
1
Order By: Relevance
“…Our study showed that QOL in PLWH was lower among PLWH in other countries [ 31 , 32 ]. In many studies, poor QOL was associated with a lower immune response, non-adherence, poor mental health, and greater disease severity [ 8 , 33 ]. Therefore, educational and supportive interventions could be designed and implemented by health sector in Kermanshah to promote the QOL in PLWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that QOL in PLWH was lower among PLWH in other countries [ 31 , 32 ]. In many studies, poor QOL was associated with a lower immune response, non-adherence, poor mental health, and greater disease severity [ 8 , 33 ]. Therefore, educational and supportive interventions could be designed and implemented by health sector in Kermanshah to promote the QOL in PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…HIV is one of the major health problems in the worldwide [ 1 8 ]. Most HIV infected people live in developing countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This definition implies that QoL is largely dependent on cultural, social and environmental contexts as well as individual perception [12,13]. QoL has been used as a criterion in assessing HIV/AIDS prevention programs, clinical treatment, and harm reduction strategies [14]. Multilevel interventions and long-term care, rehabilitation, behavioral therapy and social supports for patients receiving treatments, and application of e-health approaches can improve QoL of HIV patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published studies were carried out in United States, South Africa, India, Brazil, China, Uganda, Canada, Thailand, England, and Australia. 21 No published literature could be found on the quality of life of PLWHA in the Arab world, except one study from Lebanon conducted by Abboud and colleagues in 2010. 22 …”
Section: Introductionmentioning
confidence: 99%